Hubungan Pengetahuan, Sikap, Dan Tindakan Kesehatan Gigi dan Mulut Terhadap Indeks Gingiva Mahasiswa Fkg Universitas Jember Angkatan 2020 - Khalishah, Nadia Rizki; Dwiatmoko, Surartono; Wahyukundari, Melok Aris (Fakultas Kedokteran Gigi Universitas Jember, 2024)
DentaI and oraI heaIth of the lndonesian peopIe requires attention from health workers, because dentaI and oraI diseases are in the top ten most common diseases. Gingivitis is one of the most common dentaI and oraI diseases. One of the factors that affect dentaI and oraI heaIth is the level of knowIedge, attitudes and actions of a person to maintain dental and oral health. Knowing the reIationship of knowIedge, attitudes, and actions of dentaI and oraI heaIth on the gingival index of FKG University Jember students batch 2020. analytic observationaI research with cross sectional design. The number of samples is 60 students. Collecting data using a questionnaire regarding oral health behavior and examination of the severity of gingivitis using the gingival index. The data obtained were tabuIated and anaIyzed using the Spearman correlation test. As many as 95% of respondents have good knowledge category, 90% of respondents have good attitude category, 83.33% of respondents have good category of action, and 63.33% of respondents have healthy gingiva. The results of the Spearman correIation test showed that the significance value between variables was Iess than 0.05 (p<0.05), meaning that there was a significant reIationship between knowledge, attitudes, and oraI heaIth practices with the gingival index. There is a significant reIationship between knowIedge, attitudes, and dentaI and oral heaIth actions with the gingival index of FKG University Jember students batch 2020.